Uroven' pereokislennych lipidov krovi i funkcional'noe sostojanie immunoj sistemy u lyznikov - Volcerovskij, I. A.; Sasenkov, S. L.; Zurocka, A. V.; Uskov, G. V. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
It was determined that the blood lipoperoxidation products concentration corresponds to neutrophiles and monocytes functional activity during the examination of 278 cross-country skiers. The increase of the lipoperoxidation products concentration is the evidence of the blood immunoglobulines concentration decrease and the increase of respiratory infections possibility in athletes.